PENGEMBANGAN APLIKASI VENDING TOKEN KWH METER PRABAYAR UNTUK MENINGKATKAN EFISIENSI PENGELOLAAN LISTRIK DI APARTEMEN DAN PERUMAHAN - Sujana, Nana; Darmawan, Erwin; Sururi, Sururi (Jurnal Teknologi Komputer dan Informatika, 2025)
Efficient electricity management remains one of the primary challenges in operating modern apartments and residential complexes. The prepaid KWH meter system offers an effective solution by enabling residents to monitor and control their electricity consumption independently. This study aims to develop a Prepaid KWH Meter Token Vending Application to enhance electricity management efficiency in such environments. The application is designed to help property managers generate, distribute, and monitor electricity tokens accurately and in an integrated manner. The research methodology includes five main stages: (1) Needs analysis, conducted through interviews and direct observation to identify problems and system requirements; (2) System design, including software architecture, user interface (UI/UX), and database design; (3) Web-based application development using the CodeIgniter framework and PHP; (4) Functionality test of the application was conducted using black box testing and User Acceptance Testing (UAT) to gather user feedback; and (5) Performance evaluation to measure the efficiency improvements achieved through the application. The testing results show that the application can deliver tokens quickly and accurately, supporting effective electricity monitoring by management. This application is expected to improve operational efficiency, optimize electricity costs, and enhance comfort for residents